Two Cases of Pediatric AQP4-Antibody Positive Neuromyelitis Optica Spectrum Disorder Successfully Treated with Tocilizumab - Breu, Markus; Glatter, Sarah; Höftberger, Romana; Freilinger, Michael; Kircher, Karl; Kasprian, Gregor; Seidl, Rainer; Kornek, Barbara (Neuropediatrics, 2019)
B cell depletion with the anti-CD20-antibody rituximab is widely considered treatment of choice for long-term immunotherapy in aquaporin-4 (AQP4)-antibody positive neuromyelitis optica spectrum disorder (NMOSD). However, up to 30% of patients suffer from relapses despite complete B cell depletion. In these cases, the IL6 (interleukin-6)-receptor blocking antibody tocilizumab has been suggested as an alternative. We report two female adolescents with AQP4-antibody positive NMOSD who relapsed under rituximab treatment and clinically stabilized after switching to monthly administrations of tocilizumab. Our data suggest that early escalation of therapy with tocilizumab may lead to stabilization of disease activity in pediatric NMOSD patients who relapse under B cell depletion.
Keywords: neuromyelitis optica; tocilizumab; pediatric; AQP4; interleukin-6; plasmablasts